Validation of the continuous glucose monitoring sensor in preterm infants. (7th June 2011) - Beardsall, K; Vanhaesebrouck, S; Ogilvy-Stuart, A L; Van hole, C; Van Weissenbruch, M; Midgley, P M; Thio, M; Cornette, L; Ossuetta, I; Iglesias, I; de Jong, M; Ahluwalia, J S; et al.
Abstract : Objective: There is limited data on the use of continuous glucose monitoring in the preterm infant, particularly at extremes of glucose levels and over prolonged periods. This study aimed to assess the accuracy of the continuous glucose monitoring sensor (CGMS) across the glucose profile, and to determine whether there was any deterioration in accuracy over a 7 day period. Design: Prospectively collected CGMS data from the Neonatal Insulin Replacement Therapy in Europe (NIRTURE) Trial were compared with data obtained simultaneously using point of care glucose monitors. Setting: An international multicentre randomised controlled trial. Patients: One hundred and eighty eight very low birth weight control infants. Outcome measures: Optimal accuracy, Performance goals, Bland Altman and Error Grid analyses as well as accuracy. Results: CGMS data were found to correlate well with point of care devices for measuring glucose levels (r=0.94), with minimal bias, mean difference (95% CI) −0.02 (−1.6 to 1.7), and met the established criteria on error grid analyses. There was no deterioration in performance over time from insertion. However accuracy of individual readings to detect hypoglycaemia, or hyperglycaemia was poor. Conclusions: This data highlights that the clinical use of CGMS devices is in providing trends in glucose levels to guide in clinical management, but they can not be relied upon for diagnosing hypoglycaemia or hyperglycaemia on a single reading.